Understand electronics / Owen Bishop. - Bishop, O. N. (Owen Neville), 1927- (Newnes, 2001)
Understand Electronics provides a readable introduction to the exciting world of electronics for the student or enthusiast with little previous knowledge. The subject is treated with the minimum of mathematics and the book is extensively illustrated.